The Image of Women in The Film 'Little Woman' - Widyahening, Evy Tri (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2023)
The purpose of writing this article is to describe the image of women in the 19th century represented by the characterJo March in the film 'Little Woman' directed by Gillian Armstrong. The image of women here is the perception ofwomen in the 19th century in expressing love, career, struggle for existence and independence in making choices. Indescribing the image of women reflected in the film 'Little Woman', the researcher used a descriptive qualitativeresearch method with the type of Library research. The results showed that women in the 19th century, especiallywomen in the middle to upper social status, were considered as ideal women if they could fulfil the criteria as a womanwho could do all domestic work in the household. Women in the 19th century were more inclined to the male viewof the ideal woman at that time. The presence of the character Jo March in the film 'Little Woman' breaks the view ofthe ideal woman who must submit or obey the rules and do domestic household chores. The presence of the characterJo March shows that women also want self-actualization, independence, freedom to choose a life partner, expressfeelings, and achieve goals. In addition, the presence of Jo March as a woman who is able to actualize herself is arepresentation of most women in the 19th century who began to break the rules that restrained women's freedom inshowing their existence along with the industrial revolution at that time. This research is examined from theperspective of feminism. The film 'Little Woman' represents the image of women in the 19th century who tried toreach their dreams, love life, and independence. And the character Jo March is able to represent the women in the19th century who succeeded in achieving all their dreams.Keywords: Feminism, Women's Image, Descriptive Qualitative